A temperature‐controlled cold‐gas humidifier and its application to protein crystals with the humid‐air and glue‐coating method. Issue 4 (14th June 2019) - Baba, Seiki; Shimada, Atsuhiro; Mizuno, Nobuhiro; Baba, Junpei; Ago, Hideo; Yamamoto, Masaki; Kumasaka, Takashi
Abstract : A new temperature‐controllable humidifier for X‐ray diffraction has been developed. It is shown that the humidifier can successfully maintain protein crystal growth at a temperature lower than room temperature. Abstract : The room‐temperature experiment has been revisited for macromolecular crystallography. Despite being limited by radiation damage, such experiments reveal structural differences depending on temperature, and it is expected that they will be able to probe structures that are physiologically alive. For such experiments, the humid‐air and glue‐coating (HAG) method for humidity‐controlled experiments is proposed. The HAG method improves the stability of most crystals in capillary‐free experiments and is applicable at both cryogenic and ambient temperatures. To expand the thermal versatility of the HAG method, a new humidifier and a protein‐crystal‐handling workbench have been developed. The devices provide temperatures down to 4°C and successfully maintain growth at that temperature of bovine cytochrome c oxidase crystals, which are highly sensitive to temperature variation. Hence, the humidifier and protein‐crystal‐handling workbench have proved useful for temperature‐sensitive samples and will help reveal temperature‐dependent variations in protein structures.